2020
DOI: 10.3390/su12020736
|View full text |Cite
|
Sign up to set email alerts
|

The Uncertainty Contagion: Revealing the Interrelated, Cascading Uncertainties of Managed Retreat

Abstract: Managed retreat presents a dilemma for at-risk communities, and the planning practitioners and decisionmakers working to address natural hazard and climate change risks. The dilemma boils down to the countervailing imperatives of moving out of harm’s way versus retaining ties to community and place. While there are growing calls for its use, managed retreat remains challenging in practice—across diverse settings. The approach has been tested with varied success in a number of countries, but significant uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 58 publications
1
36
0
3
Order By: Relevance
“…Adaptation practitioners should therefore increasingly work toward the goal of developing comprehensive national adaptation plans in the Maldives that account for the complex institutional and political drivers of relocations that we point out. This also points toward the area of tension between the policy goal of moving people out of harm's way and the ties of vulnerable communities to their place (Hanna et al 2020). Including these tensions into adaptation decision-making is pivotal for successful adaptation planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptation practitioners should therefore increasingly work toward the goal of developing comprehensive national adaptation plans in the Maldives that account for the complex institutional and political drivers of relocations that we point out. This also points toward the area of tension between the policy goal of moving people out of harm's way and the ties of vulnerable communities to their place (Hanna et al 2020). Including these tensions into adaptation decision-making is pivotal for successful adaptation planning.…”
Section: Discussionmentioning
confidence: 99%
“…Managed retreat may, however, also be proactively implemented in the face of rising sea levels, albeit this is often politically difficult because coastal communities are usually reluctant to move and decision-makers that support this response face high political risks. For example, Hanna et al (2018) investigated barriers and enablers of managed retreat in New Zealand and find that a key barrier to implementing managed retreat is a lack of national policy guidance. Hence, government action on retreat has often followed extreme events or when habitability-thresholds have already been reached (Hino et al 2017;Mortreux et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Past research has shown that successful buyout efforts often rely on shared governance-based strategies to bolster local capacity (Perry and Lindell 1997;Patton and Chakos 2009), to include the role of political leadership at varied levels of government (Hanna et al 2018;Sipe and Vella 2014;Smith et al 2018). Researchers have also shown that the ability of subnational actors to adopt risk reduction efforts and deliver capacity-building programs that support local governments and individuals is highly variable (Burby and May 1997;Smith et al 2013Smith et al , 2017Smith and Vila 2020).…”
Section: Local Capacitymentioning
confidence: 99%
“…In the USA, the capacity to apply for FEMA grants that fund buyouts is particularly challenging in low wealth and smaller communities (Straub et al 2020;Mach et al 2019;Ross and Clay 2018;Smith and Vila 2020). In New Zealand, the capacity to implement buyouts is constrained by the lack of national support to build the local capacity required to implement housing acquisition projects (Hanna et al 2018;Saunders and Smith 2020). Hanna et al (2020) found that buyouts in New Zealand can be professionally, politically, financially, culturally, and socially challenging, as the necessary intergovernmental frameworks and resources are seldom in place to support effective, equitable, responsive, and robust decision-making.…”
Section: Local Capacitymentioning
confidence: 99%
“…This literature holds synergies with relational perspectives that recognise complexity and the subjective way material, technical and discursive elements come together at particular points in time and space, disperse and potentially take on new forms in the future (Blok, 2016;Neisser, 2014). A further stream acknowledges the links to decision making, such as how uncertainty can spread like a contagion between technical and political worlds (Hanna et al, 2020), the layers of potential in the ways intellectual traditions of natural and human sciences interpret riskscapes (Zahnen, 2013), or how administrative traditions influence risk management outcomes (Van Buuren et al, 2018). These all tend to highlight the importance of understanding not just what is at risk, but how risks are perceived and addressed.…”
Section: Risks Are Contingent Emergent and Uncertainmentioning
confidence: 99%